2018
DOI: 10.1155/2018/7354157
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Extreme Climate Events over Three Agroecological Zones of Southern Ethiopia

Abstract: The study aims to assess trends in extremes of surface temperature and precipitation through the application of the World Meteorological Organization’s (WMO) Expert Team on Climate Change Detection and Indices (ETCCDI) on datasets representing three agroecological zones in Southern Ethiopia. The indices are applied to daily temperature and precipitation data. Nonparametric Sen’s slope estimator and Mann–Kendall’s trend tests are used to detect the magnitude and statistical significance of changes in extreme cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 60 publications
10
28
2
Order By: Relevance
“…ough not statistically significant, a decreasing trend was observed (1.80 mm/year and 0.11 mm/year) in the lowland and highland AEZ, respectively, while an increasing trend (10 mm/year) (p < 0.05) was exhibited in the midland AEZ. e increasing trend in the ATR in the midland AEZ was in line with findings of other researchers [28,30], in which the midland AEZ experienced an increasing trend in the ATR. Likewise, Weldegerima et al [21] reported an increase in ATR in three stations in Northern Ethiopia.…”
Section: Variability and Trends In Annual Rainfall On Annual Scale supporting
confidence: 92%
See 4 more Smart Citations
“…ough not statistically significant, a decreasing trend was observed (1.80 mm/year and 0.11 mm/year) in the lowland and highland AEZ, respectively, while an increasing trend (10 mm/year) (p < 0.05) was exhibited in the midland AEZ. e increasing trend in the ATR in the midland AEZ was in line with findings of other researchers [28,30], in which the midland AEZ experienced an increasing trend in the ATR. Likewise, Weldegerima et al [21] reported an increase in ATR in three stations in Northern Ethiopia.…”
Section: Variability and Trends In Annual Rainfall On Annual Scale supporting
confidence: 92%
“…In addition, over 60% of farmers in the highland AEZ perceived an increase in rainy season temperature while a comparable proportion of farm households perceived increased temperature in the rainy season both in the midland and lowland AEZs ( Figure 7). e farmers' perception results are in line with a recent study in the same AEZs [30]. Others studies observed similar patterns in different parts of Ethiopia [25,26,32,38,39,76].…”
Section: Spotting Farmers' Perception Of Local Climate Variabilitysupporting
confidence: 90%
See 3 more Smart Citations